Signatures of niche conservatism and niche shift in the North American kudzu (Pueraria montana) invasion. Issue 8 (21st May 2015) - Callen, Steven T.; Miller, Allison J.; Thuiller, Wilfried
Abstract Aim Recent advances have improved our ability to determine the degree to which the climatic niche of invasive populations resembles (niche conservatism) or differs from (niche shift) that of native progenitors. We compared the climatic niche of kudzu (Pueraria montana), one of the most devastating invasive species in North America, between its native (East Asia) and invasive (United States) ranges. Location East Asia and United States. Methods To compare kudzu climatic niches, we calculated niche overlap, stability, unfilling (native climates not colonized in the invasive range) and expansion (invasive climates not colonized in the native range) from principal component analysis and performed niche hypothesis tests. Reciprocal ecological niche models (ENMs) examined kudzu's current versus potential distributions. To gain insight into the dynamics of different components of kudzu's niche, we performed these analyses on two climate datasets: one with variables selected by Maxent (Model M) and one with variables chosen a priori based on their putative ecological importance (Model E). Results Niche conservatism was indicated by niche similarity tests and high niche stability. Niche shift between native and invasive niches was also observed but varied with variable selection: niche unfilling was detected for Models M (0.622–0.903) and E (0.265–0.577), while expansion was found only for Model M (0.576–0.959). ENMs predicted suitable climatic habitat throughout regions in the western United States where kudzu is currently absent. Main conclusions Niche dynamics in the North American kudzu invasion are complex but can be thoroughly explored using unique variable datasets that illuminate different facets of the niche. Results presented here provide troubling evidence that kudzu has not yet occupied all climatic habitats in the United States that resemble its native range and that some invasive populations have expanded into climatically novel areas. Midwestern/western US regions appear to be most at risk for kudzu spread in the near future.